Diet, exercise, and chronic disease : the biological basis of prevention - Ardies, Curtis Murray (Boca Raton, FL : CRC Press, 2014)
'Physical activity and exercise combined with proper nutrition bring therapeutic benefits to individuals diagnosed with chronic disease. This book presents a systems biology approach to exercise and nutritional aspects of chronic disease treatment, management, and prevention. Each chapter presents clinical-based research directly related to each disease along with analysis of the associated cellular, molecular, and biochemical mechanisms. Chapters cover diet, exercise, and weight control as they relate to immune function. Diseases covered include rheumatoid arthritis, diabetes, degenerative disease, atherosclerosis, hypertension, cancer, and osteoporosis'--
'Preface The idea of producing a book on the prevention of chronic diseases through exercise and diet was intriguing for me when I was first approached with the idea. I had been teaching nutrition, exercise, and health science courses with a focus on cellular aspects of prevention for many years and had to develop all of my own materials because very few books were available. And of those that were, they had a decided clinical approach with very little discussion about the actual biochemistry or molecular mechanisms involved in prevention. When I broached the concept with several potential coauthors, the prevailing opinion was that books that covered biochemical and molecular aspects of disease etiology also were in very short supply. Thus this book was born: an attempt to collate the latest cellular- and molecularbased research on the etiology of chronic diseases with how these mechanisms of cause are modified by various aspects of diet and exercise. Essentially, we have tried to produce a text that translates molecular-based data on etiology and prevention into a clinical prescription for the prevention of chronic disease. The focus on diabetes, atherosclerosis, osteoporosis, cancer, and degenerative neurological disease is because they are the major causes of morbidity and mortality by chronic disease and also because there is sufficient molecular evidence for a strong dietary and activity (or rather, an insufficiency of both) component to their etiology. The inclusion of a separate chapter on'Inflammation' became necessary when it was clear that inflammatory signaling is a fundamental component of each of these diseases and that reducing inflammation is key to reducing risk for all of these diseases. At the time we started, obesity had not yet been declared a diseas'--
Includes bibliographical references and index.
Keywords: Chronic Disease -- prevention & control; Diet therapy; Exercise -- Physiology; Exercise therapy; Nutritional Physiological Phenomena; Physical Fitness -- Physiology; Chronic diseases -- Etiology; Nutrition; Physical fitness -- Physiological aspects; Physiology, Pathological